Contribution to the diversity and conservation knowledge of mammals in the basin of the Apurimac river, Peru - Pacheco, Víctor (2007)
The present work documents the diversity of mammals in the headwaters of the Apurímac river, one of the most important information gaps in Peru, based on an evaluation of fi ve sampling areas in the departments of Apurímac (Cconoc, Velavelayoc), Ayacucho (Yanamonte, Ccentabamba) and Cuzco (Catarata). Capture’s effort was 1280 trap-nights and 41 mistnet-nights. Sixty species were recorded in the study area and included 15 threatened species and four species endemic to Perú. As expected, bats and rodents were the most diverse orders (66,7 %). The species diversity in the sites sampled declines signifi cantly with elevation from the lowest elevation sites (Ccentabamba and Catarata) to the highest (Velavelayoc). The marsupial Monodelphis peruviana and the Dwarf Brocket deer Mazama chunyi are fifi rst records for the department of Ayacucho. The bats Artibeus planirostris and Myotis keaysi, and the river otter Lontra longicaudis are fifi rst records for the department of Apurímac. For bats, the relative abundance showed a signifi cant negative correlation with elevation, but was not signifi cant for small terrestrial mammals. The species of Sturnira, Akodon and Thomasomys had the highest values of relative abundance. The diversity indices (Shannon-Wiener and Simpson) also showed also a signifi cant negative correlation with elevation. The Apurímac river headwater is estimated to have at least 97 mammals species. We recommend creating conservation areas in Huanipaca, Yanamonte and Catarata, and enlarging the area of the Santuario Histórico Machu Picchu to include the archaeological site of Choquequirao.